The role of the inner form of word in onomasiological structures of derivative units in language and speech - Куцак, Ганна Миколаївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
The author makes an attemp to find out the status of the concept of «inner form» in onomasiology on the basis of linguistic researches and to identify the dependence of the nature of components of onomasiological structure of word from its inner form. In the article the author outlines the specific formation of onomasiological structures of naming in view of the peculiarities of the allocation of distinctive feature of named item of reality on the example of derivative units in Ukrainian modern literary language and non-usage elements of speech, and the process of transformation of the outside world in certain form as well as hyper-hyponymic differentiation of nominations is also analyzed.